Hybrid Function Projective Synchronization of Hyperchaotic Financial Systems via Adaptive Control - Vikash .; Ayub Khan; Khursheed Alam (Chaos Theory and Applications)
In this manuscript, we establish hybrid function projective synchronization of a new hyperchaotic system using an adaptive control technique with unknown system parameters. In order to prevent either from deriving from participants in the single hyperchaotic financial system, identical master and slave systems are chosen. We design an adaptive controller to achieve global chaos synchronization between these master and slave systems. The synchronization results are based on adaptive control theory and Lyapunov stability theory. Additionally, we outline the basic dynamic characteristics of both hyperchaotic financial systems. Numerical simulations performed in Matlab validate our results excellently.